Validation of a dried blood spot ceftriaxone assay in Papua New Guinean children with severe bacterial infections - Mukap, M.; Sprod, C.; Tefuarani, N.; Laman, M.; Page-Sharp, Madhu; Salman, S.; Moore, Brioni; Batty, Kevin; Davis, T.; Manning, L. (American Society for Microbiology, 2018)
© 2018 American Society for Microbiology. Dried blood spot (DBS) antibiotic assays can facilitate pharmacokinetic (PK) studies in situations where venous blood sampling is logistically and/or ethically challenging. In this study, we aimed to demonstrate the validity of a DBS ceftriaxone assay in a PK study of children with severe illness from Papua New Guinea (PNG), a setting in which health care resources are limited and anemia is common. Using a previously validated liquid chromatographytandem mass spectrometry (LC-MS/MS) assay, serial plasma and DBS ceftriaxone concentrations were measured in PNG children aged 5 to 10 years with acute bacterial meningitis or severe pneumonia. The concentration-time data were incorporated into population PK models. Ten children were recruited with an admission hematocrit of 0.22 to 0.52. Raw data demonstrated good correlation between plasma and DBS concentrations (Spearman's rank correlation coefficient [rs] =0.94 [95% confidence interval, 0.91 to 0.97], P < 0.0001). A marked systematic hematocrit bias was observed, with lower hematocrits resulting in underestimation of DBS-predicted plasma concentration. After adjustment for red cell partitioning and hematocrit bias, a population PK model comparing plasma and DBS-predicted plasma concentrations did not differ in terms of key PK parameters, including clearance, volume of distribution, and residual variability. The performance of the ceftriaxone DBS assay is robust and provides reassurance that this platform can be used as a surrogate for plasma concentrations to provide valid PK and PK/pharmacodynamic studies of severely unwell children hospitalized in a resource-limited setting. It highlights the importance of hematocrit bias in validation studies of DBS assays.